Congesting Pricing in a Road and Rail Network with Heterogeneous Values of Time and Schedule Delay - Vincent van den Berg; Erik T. Verhoef (Tinbergen Institute, 2011)
We analyse congestion pricing in a road and rail network with heterogeneous users. On the road there is bottleneck congestion. In the train there is crowding congestion. We separately analyse proportional heterogeneity that varies the values of time and schedule delay scalarly in fixed proportions and ratio heterogeneity that is in the ratio of value of time to value of schedule delay. We analyse first-best pricing and second-best pricing on only road or rail. More ratio heterogeneity lowers the relative efficiency of welfare maximisation by pricing only the road. This relative efficiency also decreases with proportional heterogeneity. Conversely, in previous research with two parallel roads, the relative efficiency of single-link pricing increased with proportional heterogeneity. This difference is caused by two road being perfect substitutes, while car and train are imperfect substitutes. The welfare gain of congestion pricing in the train is les s affected by heterogeneity. However, the relative efficiency of profit maximisation on rail only decreases with proportional and ratio heterogeneity. There are marked differences in the distributional effects on road and rail. On the road, pricing is generally more beneficial for the user the higher her value of time or schedule delay is. In the train, pricing has no distributional effects or is less beneficial the higher a user's value of time or schedule delay is.
Keywords: D62; H23; L11; R41; R48; 330; Congestion Pricing; Car Travel; Train Travel; Heterogeneity in Value of Time; Heterogeneity in Value of Schedule Delay; Substitute Modes; Bottleneck; Straßenverkehr; Straßenbenutzungsgebühr; Substitutionseffekt; Schienenverkehr; Scheduling-Verfahren